2017
DOI: 10.3892/ol.2017.5845
|View full text |Cite
|
Sign up to set email alerts
|

An unusual translocation, t(1;11)(q21;q23), in a case of chronic myeloid leukemia with a cryptic Philadelphia chromosome

Abstract: Abstract. Chronic myeloid leukemia (CML) is characterized by the translocation t(9;22)(q34;q11) [Philadelphia (Ph) chromosome). Although not frequently occurring, additional chromosome abnormalities (ACAs) can be detected at diagnosis and a number have been associated with an adverse cytogenetic and molecular outcome. The present study reports a case of CML presenting with the translocation t(1;11)(q21;q23) and a cryptic Ph chromosome. The presence of ACAs could generate greater genetic instability, promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Chronic myeloid leukemia (CML) is a hematopoietic stem cell (HSC) malignancy that results from the formation of the Philadelphia chromosome due to reciprocal chromosomal translocation t(9;22)(q34.12;q11.23), and it accounts for 15-20% of all leukemias. 1 Patients with CML need to be treated for life; moreover, the prognosis of patients with blastic transformation of CML is extremely poor. Thus, there is an unmet need to find better treatments for CML.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic myeloid leukemia (CML) is a hematopoietic stem cell (HSC) malignancy that results from the formation of the Philadelphia chromosome due to reciprocal chromosomal translocation t(9;22)(q34.12;q11.23), and it accounts for 15-20% of all leukemias. 1 Patients with CML need to be treated for life; moreover, the prognosis of patients with blastic transformation of CML is extremely poor. Thus, there is an unmet need to find better treatments for CML.…”
Section: Introductionmentioning
confidence: 99%
“…CML with the t(9;22) translocation rarely incurs the additional t(9;11) during disease progression. In the last twenty years, no more than 5 cases have been reported in the literature [ 12 14 ], and none have been reported in China. Our study found that the proportion of patients with t(9;22) accompanied by the t(9;11) translocation was even lower 0.14% (2/1382).…”
Section: Discussionmentioning
confidence: 99%
“…CML with the t(9;22) translocation rarely incurs the additional t(9;11) during disease progression. To date, no more than 5 cases have been reported in the literature [12,13,14], and none have been reported in China. Our study found that the proportion of patients with t(9;22) accompanied by the t(9;11) translocation was even lower 0.14% (2/1382).…”
Section: Discussionmentioning
confidence: 99%